2015
DOI: 10.1371/journal.pone.0118588
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation Inactivates Somatostatin and Somatostatin Receptor Type 1 in Head and Neck Squamous Cell Carcinoma

Abstract: PurposeThe aim of this study was to define somatostatin (SST) and somatostatin receptor type 1 (SSTR1) methylation profiles for head and neck squamous cell carcinoma (HNSCC) tumors at diagnosis and follow up and to evaluate their prognostic significance and value as a biomarker.MethodsGene expression was measured by quantitative RT-PCR. Promoter methylation status was determined by quantitative methylation-specific PCR (Q-MSP) in HNSCC.ResultsMethylation was associated with transcription inhibition. SST methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
(57 reference statements)
3
28
0
Order By: Relevance
“…For instance, ASNS, one risk biomarker in our study, was reported to function as a therapeutic target in castration-resistant prostate cancer [27]. SSTR1 was widely related to the progression of various cancers [28][29][30], and also functions as a prognostic marker in prostate cancer [31,32]. TRIM14 has been reported to promote invasion in glioblastoma [33] and colorectal cancer [34].…”
Section: Discussionmentioning
confidence: 57%
“…For instance, ASNS, one risk biomarker in our study, was reported to function as a therapeutic target in castration-resistant prostate cancer [27]. SSTR1 was widely related to the progression of various cancers [28][29][30], and also functions as a prognostic marker in prostate cancer [31,32]. TRIM14 has been reported to promote invasion in glioblastoma [33] and colorectal cancer [34].…”
Section: Discussionmentioning
confidence: 57%
“…In the list of 180 genes, CDH13, COL14A1, HAAO, HAND2, HS3ST2, HTR1B, NPY, and ZNF177, have been reported in endometrial cancer samples in independent studies (17-19, 21, 27). Because different cancers may have common pathways, the hypermethylated genes identified in our gene list might also be methylated in other cancers, and ADHFE1, CDO1, DPP6, EFS, FEZF2, GHSR, GRIA4, NEFL, PARP15, PAX6, SSTR1, and TRH have been reported (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). We have identified for the first time hypermethylation of BHLHE22, CCDC140, CELF4, GALNTL6, ZNF334, and ZNF662 in cancers.…”
Section: Discussionmentioning
confidence: 74%
“…Methylation of ZIC1 has been described previously for other tumor types, such as thyroid, ovarian, colon, and gastric cancer (43)(44)(45)(46). SST or somatostatin functions as an inhibitor with antisecretory, antiproliferative, and antiangiogenic effects (47) and is, in addition to cervical cancer, also found to be methylated in gastric, esophageal, colon, and head and neck cancer (48)(49)(50)(51). The biological function and expression regulation of these 3 genes in HPV-transformed cells remains to be determined.…”
Section: Discussionmentioning
confidence: 81%